The role of artificial intelligence technologies in improving the accuracy of financial forecasting within accounting information systems: A field study on a sample of companies operating in Sulaymaniyah Governorate - Abdullah, Kosrat Mohammed Abdullah; Ahmad, Prof.Dr.Rezgar Ali Ahmad (Sulaimani Journal for Humanities, 2026)
Artificial intelligence (AI) is increasingly aimed at developing accounting information systems, particularly in the field of financial forecasting. However, the effectiveness of integrating AI techniques in improving the accuracy of financial forecasting remains a research challenge requiring thorough empirical investigation. The research problem lies in determining the extent to which AI techniques contribute to enhancing the accuracy of financial forecasting within the accounting information systems of companies operating in Sulaymaniyah Governorate.The study adopted a descriptive analytical approach, and data were collected through a field survey distributed to a sample of accountants and financial managers in a number of local companies. The data were analyzed using appropriate statistical methods to test the relationship between the use of AI techniques and the accuracy of financial forecasting. The results showed that AI techniques, particularly machine learning algorithms and big data analytics, significantly contribute to improving the accuracy of financial forecasts and reducing the margin of error in future estimates. The results also indicated the presence of technical and human obstacles that limit the effectiveness of implementation, such as a lack of technical expertise and weak integration between systems. The study recommends the need to strengthen the digital infrastructure, train accounting staff on the use of AI techniques, and encourage the adoption of intelligent systems in financial institutions to support digital transformation and improve the quality of future financial decisions.
Keywords: Artificial intelligence; accounting information systems; financial forecasting; forecasting accuracy